Foreign Experience of Applying the Principle of "Pump or Pay" in the Field of Pipeline Transportation - V. I. Salygin; I. A. Guliyev; A. O. Khubaeva (Vestnik MGIMO-Universiteta, 2015)
This article reveals the practice of "ship or pay" principle in the US, Canada and Europe. The authors analyze the practice of concluding contracts for oil and petroleum products transportation, procedures, terms and conditions stipulated in the contract. The "take or pay" principle is a common practice in developed countries like the US, Canada and the UK. The specific feature of the United States is that the pipelines are not built only for one shipper, but rather for all market, which is caused the "open season" tradition. In Canada, "take or pay" principle applies to cover the capital costs of the carrier. The main reasons for usage of terms "take or pay" are to minimize risks of the carrier, building or expanding his own pipeline network, by guaranteeing shipper's financial benefits after the putting pipeline into operation. "Take or pay" contracts cover the carrier's obligation to provide agreed minimum amount of petroleum to the consignor within a certain period. In turn, the shipper is obliged to accept the minimum amount of petroleum and pay, regardless of the fact of acceptance of oil. "Take or pay" principle is a kind of risk-sharing mechanism, which allows to shift the risks of non-fulfillment of the contract to the shipper. Besides, the "take or pay" principle can be indirect guarantee in the context of project financing, and therefore, financing. The article emphasizes the main advantages of the application of this principle and opportunities for its use in Russia.